What drives Basel III implementation? A cross-country empirical investigation - Feridun, Mete (Routledge Journals, Taylor & Francis Ltd, 2025)
This article empirically explores the factors driving cross-country Basel III implementation progress for 20 countries using a novel dependent variable drawn from the Basel Committee's Progress Report. Results suggest that implementation of Basel III reforms is at a more advanced stage in countries with strong banking sectors, credible governments, more stable political systems and transparent public sectors.
Keywords: Basel standards; Basel committee; BCBS; banking regulation